1600. Closing the gap on moxifloxacin breakpoints for Stenotrophomonas maltophilia - Stone, Tyler J (Open Forum Infect Dis, 2020)
BACKGROUND: Moxifloxacin (MOX) has in vitro activity against Enterobacterales and Stenotrophomonas maltophilia (SM). Although MOX commonly displays lower minimum inhibitory concentration (MIC)(50/90) values against SM when compared to levofloxacin, there are currently no established MOX breakpoints for treatment of SM. The Clinical and Laboratory Standards Institute (CLSI) has established interpretive categories and MIC breakpoints for levofloxacin (S ≤2µg/ml) against SM. The US Food and Drug Administration and European Committee on Antimicrobial Susceptibility Testing provide MOX breakpoints for Enterobacterales with susceptible MICs represented at ≤ 2 µg/mL and ≤ 0.25 µg/mL, respectively. The purpose of this study was to evaluate MOX MIC distribution against SM strains recovered from clinical specimens. METHODS: Clinical samples from patients with suspected infection during calendar year 2018 and 2019 were processed in the microbiology lab of Wake Forest Baptist Medical Center. After incubation, SM colonies were identified by MALDI-TOF system. MOX susceptibility testing was performed for these clinical isolates by gradient diffusion strip methodologies. Results were displayed as MIC (µg/mL) without interpretation. MIC(50/90) and susceptibility rates at potential breakpoints were calculated. RESULTS: A total of 211 isolates were tested, 112 from 2018 and 99 from 2019. MOX MIC(50) and MIC(90) for all isolates was 0.25 µg/mL and 2 µg/mL, respectively. The range of MIC distribution was ≤ 0.006 µg/mL to ≥ 64 µg/mL. Percent susceptibilities at incremental MICs, including established MOX breakpoints against Enterobacterales and established levofloxacin breakpoints against SM, are represented in Table 1. MIC distribution was plotted in Figure 1. Table 1. Susceptibility rates of S. maltophilia to moxifloxacin at theoretical breakpoints [Image: see text] Figure 1. Moxifloxacin MIC Distribution against All S. maltophilia Isolates [Image: see text] CONCLUSION: With no established breakpoint, these data represent one of the largest samples of MOX MICs against SM in the United States. Using the CLSI breakpoint for levofloxacin in SM (MIC of ≤2ug/ml) the overall susceptibility rate is 93%. This finding highlights the importance of performing susceptibility testing to this agent by the microbiology laboratory and the critical need for MOX breakpoints in SM. DISCLOSURES: Tyler J. Stone, PharmD, Paratek (Research Grant or Support) John Williamson, PharmD, Paratek (Research Grant or Support) Elizabeth Palavecino, MD, Paratek (Grant/Research Support)Paratek (Grant/Research Support)